2020
DOI: 10.3390/ijms21062231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Resveratrol/Quercetin Mixture on the Reversion of Hypertension Induced by a Short-Term Exposure to High Sucrose Levels Near Weaning and a Long-Term Exposure That Leads to Metabolic Syndrome in Rats

Abstract: Hypertension is an important global public health problem. Excess sucrose during a short period near weaning (short sucrose period, SSP; sucrose during rat postnatal days 12 to 28) increases the risk of developing hypertension during adulthood and sucrose ingestion for 6 months after weaning also results in metabolic syndrome (MS) accompanied by hypertension. The aim of this study was to test if the mechanisms that lead to hypertension induced by SSP and MS are similarly modified by a resveratrol/quercetin mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The authors of [ 43 ] found evidence that resveratrol, an anti-inflammatory and antioxidant substance, is an effective activator of SIRT1 [ 10 ]. In addition, SIRT1 overexpression in the rostral ventrolateral medulla (RVLM), another central region that regulates sympathetic activity, led to lower blood pressure and reduced sympathetic outflow by lowering ROS levels in spontaneously hypertensive rats [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [ 43 ] found evidence that resveratrol, an anti-inflammatory and antioxidant substance, is an effective activator of SIRT1 [ 10 ]. In addition, SIRT1 overexpression in the rostral ventrolateral medulla (RVLM), another central region that regulates sympathetic activity, led to lower blood pressure and reduced sympathetic outflow by lowering ROS levels in spontaneously hypertensive rats [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more clinical trials need to be conducted to clarify the effects of RSV on blood pressure. Novel methods used to enhance the efficacy of RSV in treating hypertension, such as combining RSV with other compounds [ 92 ] and using nanocarriers [ 93 ], are also worthy to be further developed.…”
Section: Clinical Trials Of Rsv In the Treatment Of Vascular Metaboli...mentioning
confidence: 99%
“…An elevated sucrose ingestion which leads to OS has been associated to the development of hypertension. We have previously published that the administration of sucrose during a short period near weaning in rats (postnatal days 12 to 28) increases the risk of developing hypertension when the organisms reach adulthood and that this elevation in blood pressure is accompanied by OS [ 195 , 196 ].…”
Section: Oxidative Reductive and Nitrosative Stress Effects On Ementioning
confidence: 99%
“…SOD reduces the ROS that uncouple eNOS and increase NO levels [ 199 ]. SIRT3 was found to be decreased at the end of a short period near weaning when rats received sucrose [ 195 , 196 ].…”
Section: Oxidative Reductive and Nitrosative Stress Effects On Ementioning
confidence: 99%